Shelterin promotes tethering of late replication origins to telomeres for replication‐timing control. (11th July 2018) - Ogawa, Shiho; Kido, Sayuri; Handa, Tetsuya; Ogawa, Hidesato; Asakawa, Haruhiko; Takahashi, Tatsuro S; Nakagawa, Takuro; Hiraoka, Yasushi; Masukata, Hisao
Abstract: DNA replication initiates at many discrete loci on eukaryotic chromosomes, and individual replication origins are regulated under a spatiotemporal program. However, the underlying mechanisms of this regulation remain largely unknown. In the fission yeast Schizosaccharomyces pombe, the telomere‐binding protein Taz1, ortholog of human TRF1/TRF2, regulates a subset of late replication origins by binding to the telomere‐like sequence near the origins. Here, we showed using a lacO /LacI‐GFP system that Taz1‐dependent late origins were predominantly localized at the nuclear periphery throughout interphase, and were localized adjacent to the telomeres in the G1/S phase. The peripheral localization that depended on the nuclear membrane protein Bqt4 was not necessary for telomeric association and replication‐timing control of the replication origins. Interestingly, the shelterin components Rap1 and Poz1 were required for replication‐timing control and telomeric association of Taz1‐dependent late origins, and this requirement was bypassed by a minishelterin Tpz1‐Taz1 fusion protein. Our results suggest that Taz1 suppresses replication initiation through shelterin‐mediated telomeric association of the origins at the onset of S phase. Synopsis: Replication‐timing control of late‐firing origins in fission yeast chromosome arms involves Taz1 shelterin‐mediated tethering of the origins to the proximity of telomeres, where replication initiation is inhibited independent of subnuclear localization. Internal Taz1‐dependent late replication origins are localized close to telomeres in G1/S. Shelterin components are necessary for replication‐timing control and origin localization. Nuclear periphery localization is not necessary for late‐timing control. A Tpz1‐Taz1 fusion "mini‐shelterin" restores late‐timing control and telomeric association of origins. Abstract : Timing control of late‐firing chromosome arm origins in fission yeast involves Taz1‐mediated origin tethering to the proximity of telomeres, where replication initiation is inhibited independent of subnuclear localization.